The Swedish budget 1966/67 - Sweden (Stockholm : Ministry of Finance, 1966)
This fourth edition of The Swedish Budget contains a summary of the draft budget for the fiscal year 1966/67, with more detailed reviews of the main items of government expenditure. The budget statement is presented in a slightly abridged version. A summary is also given of the main reforms in the 1965/66 budget.
A summary published by the ministry of Finance
rpm 20/02/2019
Ref
Keywords: Budget; Budget; Economic history; Sweden; Sweden